The Development of Islamic Mutual Funds in Indonesia: A Bibliometric Analysis using VosViewer - Batubara, Mi'raj Faizal; Siregar, Saparuddin (Journal of Islamic Economics Literatures, 2024)
This study aims to evaluate and analyze the development of research on "Islamic Mutual Fund in Indonesia" in Indonesia. Using a descriptive qualitative approach and meta-analysis, data was collected from 171 journal articles indexed in the Dimensions database until July 1, 2024. The data collection process was conducted by searching for journal publications using the keyword "Islamic Mutual Fund in Indonesia" and selecting relevant articles based on certain criteria, including the requirement for a DOI. The analysis was conducted using VOSviewer software to perform a detailed bibliometric analysis, including author maps and keyword maps that show trends and co-occurrences in related publications. The results show that the topic of Islamic Mutual Fund in Indonesia is most widely discussed in the category of "Commerce Management Tourism and Services", followed by "Economics" and "Philosophy and Religious Studies". This research provides an overview of the collaboration network structure and relationships between authors in the scientific network as well as identifying trends and patterns in Islamic Mutual Fund in Indonesia research.